Tetralogy of Fallot with pulmonary valve agenesis - Elizabeth Janet de la Paz-Loret de Mola; Luis Lorenzo Céspedes-Sellén; Elizabeth Sellén-Sanchén; Carlos Manuel Oliva-de Céspedes (Universidad Médica Pinareña, 2021)
Introduction: tetralogy of Fallot with pulmonary valve agenesis is a complex congenital heart disease, with a prevalence of 2-6%, frequently associated with chromosomopathies.